2018
DOI: 10.1016/j.bioactmat.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol functionalized carbon nanotubes/gelatin-chitosan nanocomposite: An approach for significant drug release

Abstract: This research work blooms the new idea of developing a safe and controlled drug releasing matrix using multi-walled carbon nanotubes (MWCNTs). In aqueous solution, uniform and highly stable dispersion of MWCNTs was obtained after secondary functionalization with polyethylene glycol (PEG) which was studied by Fourier transmission infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA). Solution casting method was used to prepare MWCNTs/gelatin-chitosan nanocomposite films and the effect of MWCNTs on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 48 publications
3
41
0
Order By: Relevance
“…6 c, significant weight loss observed in the range of 200–600 °C in MWSB-PEG suggests the amino functional groups were thermally stable and they could take part in some chemical reactions with a temperature of 600 °C and above. A comparable observation also reported by a group of researchers on the drug release study for PEG-functionalised MWCNT incorporated with gelatin and CHI 48 . They discovered that the thermal decomposition of carboxylated and PEG-grafted MWCNT occurred between 90 and 600 °C with MWCNT-PEG resulted in the highest weight loss overall.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…6 c, significant weight loss observed in the range of 200–600 °C in MWSB-PEG suggests the amino functional groups were thermally stable and they could take part in some chemical reactions with a temperature of 600 °C and above. A comparable observation also reported by a group of researchers on the drug release study for PEG-functionalised MWCNT incorporated with gelatin and CHI 48 . They discovered that the thermal decomposition of carboxylated and PEG-grafted MWCNT occurred between 90 and 600 °C with MWCNT-PEG resulted in the highest weight loss overall.…”
Section: Resultssupporting
confidence: 89%
“…All tests were conducted in PBS (pH 6.8–7.4) as the dissolution media for the drug release study. Samples Drug loaded Maximum drug released (%) Overall time released (min) Ref MWCNT-COOH/gelatin-CHI MWCNT-PEG/gelatin-CHI Ciprofloxacin lactate (10 μg) 97.5 98.1 90 48 MWCNT Dipyridamole (50 wt%) 40.0 60 51 MWCNT-COOH Griseofulvin Sulfamethoxazole (N/A) 80.0 80.0 120 52.5 52 MWCNT-PEG Methotrexate (56.5 wt%) 44.2 1680 53 MWCNT-COOH 6 mercaptopurine (65 wt%) 96.1 1200 54 MWCNT-glucose/starch Zolpidem (75 wt%) 64.0 4320 55 …”
Section: Resultsmentioning
confidence: 99%
“…Concerning the MWCNTs, several studies have described their application in the production of composites that substantially hinder biofilm growth. The fact is, whether through the use of thin organic films of MWCNT/poly(N-vinylcarbazole), MWCNT/polyethylene composite disks, or the application of drug-loaded MWCNT-PEG/gelatin-chitosan nanocomposites, significant cell viability losses associated with Gram-negative and -positive bacteria could already be achieved ( Santos et al., 2012 ; Jing et al., 2018 ; Sharmeen et al., 2018 ). Another study also demonstrated good antimicrobial properties of electrospun nanofibers consisting of lignin-decorated thin MWCNTs (t-MWNTs) incorporated in poly(vinyl alcohol) ( Lee et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the reviewed studies, the conjugation of CNTs with silver or titanium plays an important role in decreasing CNTs' toxicity ( Subbiah et al., 2011 ; Seo et al., 2014 ; Karthika et al., 2018 ; Chaudhari et al., 2019 ). Likewise, the incorporation of CNTs into polymeric matrices was also effective in suppressing its toxicity ( Subbiah et al., 2011 ; Nie et al., 2017 ; Sharmeen et al., 2018 ). However, although the results are promising, further research is needed to clarify the effects of CNTs on biological systems.…”
Section: Resultsmentioning
confidence: 99%
“…Different nanotubes have been proposed with this aim and different possibilities. Despite carbon nanotubes (CNTs) have attracted most interest, other nanotubes are being studied as potential drug carriers in medicine and pharmacy [52,53,54,55], e.g., titanate and titania nanotubes (TiNTs) [56,57], hydroxyapatite (HApNTs) [58] and zinc oxide (ZnONTs) [59]. One important drawback of nanotubes is their synthesis process, which is, usually, complex and expensive.…”
Section: Introductionmentioning
confidence: 99%